Machining Duplex Stainless Steel: Comparative Study Regarding End Mill Coated Tools - Gouveia, Ronny M. (2016)
The difficulties in the machining of duplex stainless steel are well known. However, research on this matter is rather limited. Suppliers offer quite different cutting tools for the same raw material, with end mills of two, three or even four knives and a huge number of distinct coatings, some of them under commercial brands, making it difficult to assess the advantages they offer. Furthermore, there is a remarkable difference among the several types of duplex stainless steel available nowadays on the market. The present work intends to assess the machining performance of different tools, analyzing the behavior and wear mechanisms with two different cutting lengths, keeping constant the machining trajectory. Some other parameters were also kept constant, such as cutting speed, depth of cut and cutting width, as well as feed per tooth. The machining process was carried out under lubricated conditions, using an emulsion of 5% oil in water. Tools provided with a different number of teeth and surface coatings were tested, analyzing the wear behavior of each cutting length using scanning electron microscopy, trying to identify wear performance and how each coating contributes to increased tool life. The surfaces produced were also analyzed by means of profilometry measurements, correlating tool wear and part surface roughness. This comparative study allows determining the advantages of different tools relative to others, based on coatings and tool geometry.